Assessment of groundwater quality for irrigation and drinking purposes in the Limpopo Granulite-Gneiss region, Limpopo Province, South Africa - Claassen, Marius (University of Pretoria, 2025)
Mini Dissertation (MSc (Water Resource Management))--University of Pretoria, 2024.